2006
DOI: 10.4049/jimmunol.176.4.2617
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α Blockade Down-Regulates the CD40/CD40L Pathway in the Mucosal Microcirculation: A Novel Anti-Inflammatory Mechanism of Infliximab in Crohn’s Disease

Abstract: The CD40/CD40 ligand (CD40L) pathway is involved in Crohn’s disease (CD) pathogenesis. In the patients’ circulation, soluble CD40L (sCD40L) levels are elevated and surface CD40L is increased in platelets and T cells, whereas in the intestine CD40 is overexpressed in the microvasculature and CD40L in platelets and T cells. The therapeutic effects of infliximab in CD are attributed to its systemic anti-TNF-α action, but because TNF-α modulates both CD40 and CD40L, we investigated whether infliximab affects the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(109 citation statements)
references
References 54 publications
5
102
1
1
Order By: Relevance
“…The sCD40L is another important platelet-derived factor that has been correlated with disease activity and extent in CD [23], as well as with tissue response to infliximab [24]. Similarly to PF4 determined by ELISA, sCD40L serum levels observed before treatment were not associated with response to infliximab, nor correlated to PF4 peaks on SELDI-MS.…”
Section: Discussionmentioning
confidence: 94%
“…The sCD40L is another important platelet-derived factor that has been correlated with disease activity and extent in CD [23], as well as with tissue response to infliximab [24]. Similarly to PF4 determined by ELISA, sCD40L serum levels observed before treatment were not associated with response to infliximab, nor correlated to PF4 peaks on SELDI-MS.…”
Section: Discussionmentioning
confidence: 94%
“…1). Danese et al [51] showed that INF significantly reduced levels of intestinal endothelial expressed CD40 and VCAM-1 in treated patients with CD, as well as their levels of soluble CD40L.…”
Section: Effects On Cd40-cd40l and Lymphocyte Homingmentioning
confidence: 99%
“…23 Anti-TNF therapeutics dampens inflammation in IBD, at least in part, by modulating the gut microbiota, inducing T cell apoptosis, and by inhibiting vasculitis. 25,26 With respect to the microbiota, this decreased inflammation is associated with modulation of the gut microbiota tending toward eubiosis. The microbiome of treated individuals was characterized by reduced Enterobacteriaceae (specifically E. coli) and Ruminococcus, and increased proportions of Bacteroidetes and Firmicutes, restoring the microbiome to a composition more reflective of healthy individuals.…”
Section: Introductionmentioning
confidence: 99%